Laki-laki tidak boleh nangis: Pentingnya pendekatan alternatif dalam mengeksplorasi pengalaman lelaki Indonesia dalam relasi romantis - Karel Karsten Himawan (Konsorsium Psikologi Ilmiah Nusantara, 2022)
Academic discourses around interpersonal relationship in the patriarchal culture tends to assume men in the superior position, hence their unique experience is considered less significant to be investigated. As a result, what we know about men’s experience and expectation in a romantic relationship is only as far as what their gender stereotype subscribes; that relationship is only for sex, status and power exercise, and social symbol. In the present editorial note, I emphasize the urgency to utilize an alternative approach in exploring unique experience of Indonesian men in romance; such insight would be valuable to improve the quality of interpersonal relationship through culturally-informed perspective.